2022
DOI: 10.3390/f13111751
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Characteristics of Soundscape Ecology in Urban Forest Areas and Its Landscape Spatial Influencing Factors

Abstract: We explored the spatial and temporal characteristics of the urban forest area soundscape by setting up monitoring points (70 × 70 m grid) covering the study area, recorded a total of 52 sound sources, and the results showed that: (1) The soundscape composition of the park is dominated by natural sounds and recreational sounds. (2) The diurnal variation of sound sources is opposite to that of temperature, 6:00–9:00 is the best time for the public to perceive birdsong, and after 18:00, the park is dominated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Landscape design forms and elements can affect the types, diversity, and significance of sounds in a green space, resulting in a wide range of soundscape quality [55,65,68,69].…”
Section: Vol 45 Pt 3 2023mentioning
confidence: 99%
See 2 more Smart Citations
“…Landscape design forms and elements can affect the types, diversity, and significance of sounds in a green space, resulting in a wide range of soundscape quality [55,65,68,69].…”
Section: Vol 45 Pt 3 2023mentioning
confidence: 99%
“…Positive soundscape quality can be described as a combination of "naturalness", "diversity" and "appropriateness" [65]. Several studies found that the presence of natural sounds in green spaces resulted in increased preference, pleasantness, perceptions of tranquillity and health and wellbeing outcomes [65,68,[70][71][72]. Nature sound preference was also found to be dependent on several factors, such as gender, age, cultural background, living environment and behavioural and psychological elements [70,71].…”
Section: Vol 45 Pt 3 2023mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao, Yujie, et al highlight that effective management of the acoustic environment is crucial for enhancing overall livability. By thoughtfully integrating and utilizing sounds in our surroundings, we can significantly improve the quality of life for residents, fostering positive and harmonious living experiences [4]. These connections arise as people develop an understanding of, and attribute value to, those places.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, a well-maintained acoustic environment in a historical space is essential for preserving the authenticity and cultural importance of the area. The significance of soundscapes in shaping the historical ambiance and enhancing the perception of culture and landscape has been increasingly acknowledged and appreciated [1][2][3][4][5][6][7]. Leus and Herssens highlight the significance of conserving the entire sensory and natural experience of historical landscapes during renovation and conservation efforts.…”
Section: Introductionmentioning
confidence: 99%